Pengaruh Penggunaan Video Pembelajaran Berbasis Problem Based Learning (PBI) terhadap Hasil Belajar Siswa Kelas XI SMA pada Materi Termokimia - Sintia, Melly; Jasmidi, Jasmidi (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Problem Based Learning (PBL) learning model is a set of learning activities that emphasize the process of solving problems faced scientifically. The use of video media can help students' learning process and will have a big impact on the learning outcomes of thermochemical material because almost everyone, from children to the elderly, now has a smartphone. In addition to learning videos, powerpoint is one of the learning media that can help students who have learning difficulties. The purpose of this study was to determine whether the thermochemistry learning outcomes taught using PBL-based learning videos were higher than the thermochemistry learning outcomes taught using PBLbased PPT. This study involved the experimental class I and the experimental class II. From the results of the study, the average pre-test for the experimental class I was 41,95 and the experimental class II was 41.44. After being treated with learning in both experimental classes, post-test was then recommended to determine learning outcomes, the post-test average of experimental class I was 83.14 and experimental class II was 78.44. The results showed that the experimental class I which was taught by learning video media and the PBL model was higher than the learning outcomes of the experimental class II which was taught by the powerpoint media and the PBL model. It can be concluded that the use of instructional video media, learning outcomes are higher than the use of powerpoint media.